Ontologia do espaço, globalização e técnica: um diálogo entre Sloterdijk e a geografia - Vieira, Lucas Pereira (2024)
The research aims to establish a dialog between the theory of geography and the philosophical thought developed by Peter Sloterdijk. To this end, parallels are sought to be drawn between the way in which geographic science has dealt with relevant themes in its internal framework, privileging debates around the ontology of space, technique, and globalization. It also aims to analyze how these same phenomena are recurrently thematized, occupying a fundamental position in Sloterdijk's philosophy. The themes that guide this investigation, namely, the ontology of space, globalization, and technique, were not selected arbitrarily. Besides being well-established issues within the research area of geographic science, they are notions of fundamental importance for understanding Sloterdijk's thought. It is worth noting that, although these and other diverse themes dear to the geographical discipline are frequently worked on by the philosopher in question, his work is not a work that is located within the internal plane of the theory of geography, after all, Sloterdijk does not expressly intend to develop a proposal focused on geographic science. However, this fact does not prevent, as intended in this research, that geographic science can embark on a project of aspiring to a philosophical basis to (re) think established themes in the discipline. Especially when identifying the potential that Sloterdijkian philosophy can offer and the still incipient nature of its reception by the theory of geography.